Improving the social skills of elementary school students through traditional games - Tawakal; Imran Fadhil; Alyadi S; Mahmudin Aritanoga; Agung Cahyadi (Pelita International Publishing, 2024)
Traditional games in today's millennial era are almost unheard of, but most children today spend their free time playing modern games such as smartphones. Seeing this phenomenon makes us concerned because the effects of frequent students playing modern games on gadgets such as smartphones decrease students' social levels. This can be seen from the observations made at State Elementary School (SD Negeri 54 Banda Aceh); children prefer individual activities, are difficult to regulate, and like to argue. The study aimed to determine whether the traditional game of Englolibaba biscuits can improve students’ social skills. This research uses the action research method, which includes planning, action, observation, and reflection. The action given was the traditional game of Englolibaba biscuits. Data collection techniques in this study were observation, interview, and documentation. The sample in this study amounted to 20 fifth-grade students. The results showed increased students' social skills given the action of the traditional game of Englolibaba biscuits. This was proven based on the significant level, where the results stated a significant difference between the pre-test and post-test results. So, it can be concluded that there is an increase in students' social skills after being given the traditional game of Englolibaba biscuits.